Mediating the Maltreatment–Delinquency Relationship: The Role of Triad Gang Membership - Chui, Wing Hong (Journal of interpersonal violence, 2021)
The primary aim of this article is to examine the role of triad affiliation in mediating the relationship between child maltreatment (neglect, punishment, emotional abuse, and sexual abuse) and delinquency among active young gang members in Hong Kong. A sample of 177 gang members aged 12 to 24 was recruited to complete a questionnaire with the assistance of a youth outreach social work team. Neglect was identified as the most common form of maltreatment, followed by emotional abuse, punishment, and sexual abuse. Mediation analyses confirmed that triad affiliation acts as a mediating variable in the child maltreatment–delinquency relationship, except in cases of sexual abuse. Only the relationship between punishment and delinquency was found to be fully mediated by triad affiliation; partial mediation effects were found for neglect and emotional abuse. Recommendations for child protection and youth workers are provided.